Mechanism of abscisic acid in promoting softening of postharvest ‘Docteur Jules Guyot’ pear (Pyrus communis L.) - Xu, Xiaofei; Zhu, Xinxin; Jiang, Fudong; Li, Qingyu; Zhang, Aidi; Zhang, Hongxia; Li, Jianzhao (Frontiers in Plant Science, 2024)
Abscisic acid (ABA) is a key hormone in plant growth and development, playing a central role in responses to various biotic and abiotic stresses as well as in fruit ripening. The present study examined the impact of ABA and nordihydroguaiaretic acid (NDGA) on various postharvest 'Docteur Jules Guyot' pear fruit characteristics, including firmness, pectinase activity, pectin content, volatile aromatic substances, and the expression of correlated genes. The results showed that ABA quickly reduced fruit firmness, increasing the activity of pectin degradation-related enzymes. The contents of water-soluble pectin (WSP) and ionic-soluble pectin (ISP) increased, and covalent binding pectin (CBP) decreased under ABA treatment. Among the detected volatile aromatic substances, the highest level substance of the fruit was ester, and the ABA treatment significantly promoted the amount of ester substances. The cell wall disassembly-related genes PcPME3, PcPG1, PcPG2, PcPL, PcARF2, and PcGAL1, as well as ABA biosynthesis-related genes PcNCED1 and PcNCED2, were also significantly induced by ABA. Conversely, all these genes were repressed in the NDGA treatment group. Therefore, it was speculated that ABA may promote the softening of postharvest European pear fruit by affecting the activity of pectin degradation enzymes in fruit cell walls.